Ultra–low-contrast transfemoral TAVI using the MyVal transcatheter heart valve: a prospective single-center feasibility and safety study - Georgios E. Papadopoulos; Ilias Ninios; Maria Kalaitzoglou; Sotirios Evangelou; Andreas Ioannides; Athinodoros Nikitopoulos; Georgios Bompas; Vlasis Ninios; Grigorios Giamouzis (Frontiers in Cardiovascular Medicine, 2026)
Background Acute kidney injury remains clinically relevant after transcatheter aortic valve implantation (TAVI), particularly in chronic kidney disease, and iodinated contrast is a modifiable procedural contributor. Methods We conducted a prospective single-center study of 50 patients undergoing transfemoral TAVI with an intraprocedural ultra–low-contrast strategy using the MyVal transcatheter heart valve. The primary feasibility endpoint was successful TAVI completion with total intraprocedural contrast volume ≤10 mL. Procedural outcomes, valve performance, renal function, and 30-day clinical events were assessed. Contrast-enhanced cardiac CT angiography was used for planning. Median CT contrast volume was 45 mL; median CT-to-TAVI interval was 18 days. Exploratory 6-month renal and clinical follow-up was analyzed when available. Results Ultra–low-contrast MyVal TAVI was completed in all patients, with median contrast volume 8 mL [interquartile range, 6–10] and no procedure exceeding 10 mL. Baseline renal impairment was frequent, with median estimated glomerular filtration rate 38 mL/min/1.73 m 2 and 15 patients having estimated glomerular filtration rate <30 mL/min/1.73 m 2 . Technical success was achieved in 50 patients, with no intraprocedural death, coronary obstruction, annular rupture, valve embolization, second valve implantation, or emergency surgery. Valve hemodynamics improved, with mean aortic gradient decreasing from 45.2 ± 11.8 mmHg at baseline to 8.7 ± 3.2 mmHg at 30 days, and no moderate or severe paravalvular regurgitation. Renal function remained stable, with no significant creatinine increase and modest estimated glomerular filtration rate increase at 30 days. Acute kidney injury occurred in 1 patient and was limited to stage 1; no patient developed stage 2 or 3 acute kidney injury or required new renal replacement therapy. Among patients with 6-month laboratory follow-up, renal function remained stable or improved, and no patient initiated renal replacement therapy. Conclusions In this single-center feasibility study, an intraprocedural ultra–low-contrast transfemoral TAVI strategy using the MyVal valve was feasible, with preserved early procedural success and valve performance. Renal function remained stable through 30 days, and AKI was infrequent; however, without a comparator group, these findings should be interpreted as descriptive feasibility and early safety observations rather than evidence of renal protection, AKI reduction, or superiority over standard contrast-guided TAVI. Larger comparative studies are required.